2016
DOI: 10.1007/s10533-016-0234-4
|View full text |Cite
|
Sign up to set email alerts
|

The UK’s total nitrogen budget from 1990 to 2020: a transition from source to sink?

Abstract: This study estimates the annual total nitrogen balance of the UK from 1990 to 2020. The following inputs of nitrogen are considered: inorganic fertilizer, atmospheric deposition; food and feed imports; and biological nitrogen fixation. The outputs considered compose: atmospheric emissions; direct losses of sewage and industrial effluent to the sea; fluvial losses at source; food and feed exports; and terrestrial denitrification. It is shown that: (1) Inputs of inorganic fertilizer declined significantly over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The intercept value ( α ) represents the average BOD conditions accounting for differences in sampling across the factors considered in this study and so the trend in the intercept represents sites where BOD is changing. Previous studies have shown that BOD has declined across the UK (Worrall, Burt, et al., 2016) and such decreases in BOD have been led by regulation such as the Urban Waste Water Treatment Directive (European Commission, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The intercept value ( α ) represents the average BOD conditions accounting for differences in sampling across the factors considered in this study and so the trend in the intercept represents sites where BOD is changing. Previous studies have shown that BOD has declined across the UK (Worrall, Burt, et al., 2016) and such decreases in BOD have been led by regulation such as the Urban Waste Water Treatment Directive (European Commission, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The comparative freshwater temperature data given in Table 2 shows that for both the lake and final sewage waters sampled in remove nutrients but can also include measures to lower the organic matter, and indeed the impact of the UWWTD on water quality has already been demonstrated for phosphorus (Civan et al, 2018), nitrogen (Worrall et al, 2016), particulates (Worrall et al, 2014); and DOC (Worrall et al, 2018), this it would be expected, a priori, that the UWWTD would have altered the supply of hot water to surface waters. Despite the demonstrated warming effect of sewage effluent (Kinouchi et al, 2007) Walker et al (2004) go further and describe four critical aspects of resiliencelatitude, resistance, precariousness, and panarchy.…”
Section: Discussionmentioning
confidence: 99%
“…by 2005 and by then the United Kingdom was 99% compliant. Implementation of the UWWTD can include interventions to remove nutrients but can also include measures to lower the organic matter, and indeed the impact of the UWWTD on water quality has already been demonstrated for phosphorus (Civan et al, 2018), nitrogen (Worrall et al, 2016), particulates (Worrall et al, 2014); and DOC (Worrall et al, 2018), this it would be expected, a priori, that the UWWTD would have altered the supply of hot water to surface waters. Despite the demonstrated warming effect of sewage effluent (Kinouchi et al, 2007), we do not know whether changes implemented to improve water quality would change the volume or temperature of the final sewage effluent.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the N budget have been conducted to improve the general understanding of the N cycle, environmental consequences of increased N application to croplands, and possible strategies for achieving sustainable intensification of crop production at global [15,16] or national scale [8,17]. The ecosystem of crop production is threatened by the increased N input and declining N use efficiency (NUE) in China, and exploring the trends in various N inputs to the croplands and NUE in China's crop production is vital for agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%